2016
DOI: 10.23937/2474-3674/1510015
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Moral Distress in Critical Care Nurses: A Pilot Study

Abstract: Background: Moral distress can affect critical care nurses caring for complex patients. It can result in job dissatisfaction, loss of capacity for caring, and nurse turnover, resulting in a negative impact on quality care.Aim: This study purpose was to determine how moral distress impacts critical care nurses (adult and pediatric) and to implement improvement strategies to reduce moral distress, improve job satisfaction, and retention.Theoretical framework: Nathaniel's Theory of Moral Reckoning was the grounde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(65 citation statements)
references
References 18 publications
3
62
0
Order By: Relevance
“…The results of this study showed that the nurses in intensive care units participating in this study had a low average score of moral distress. In line with the present study, Fumis in Brazil [26], Allen in the United States [27] and Karagozoglu in Turkey [28] all showed some degree [29], Etebari in Ardabil [30], Sadeghi in Shahroud [31], and Ashktorab in Tehran [32] showed the moral distress in nurses. While Wenwen et al in China [33] confirmed less moral distress in nurses in intensive care units.…”
Section: Discussionsupporting
confidence: 88%
“…The results of this study showed that the nurses in intensive care units participating in this study had a low average score of moral distress. In line with the present study, Fumis in Brazil [26], Allen in the United States [27] and Karagozoglu in Turkey [28] all showed some degree [29], Etebari in Ardabil [30], Sadeghi in Shahroud [31], and Ashktorab in Tehran [32] showed the moral distress in nurses. While Wenwen et al in China [33] confirmed less moral distress in nurses in intensive care units.…”
Section: Discussionsupporting
confidence: 88%
“…[7,16,17] Most studies conclude that moral distress in healthcare professionals can escalate to burnout, increased medico-legal errors and increased turnover, all of which impact negatively on the quality of healthcare provided to patients and their significant others. [5,18] In contrast, a study by Henrich et al [19] revealed that the presence of moral distress positively impacted healthcare workers by increasing their vigilance and compassion for critically ill patients. Bearing in mind the negative consequences of moral distress on healthcare professionals working in CCUs, hospital managements may institute strategies such as counselling and debriefing sessions to assist CCNs cope with moral distress.…”
Section: Discussionmentioning
confidence: 98%
“…In circumstances where patients are treated in the ICU for an extended period (e.g., due to terminal condition, advanced age, or multi-organ dysfunction), moral distress can be a common experience among healthcare professionals. Many factors have been identified to be positively correlated with high moral distress among ICU staff such as job dissatisfaction, high patient-healthcare ratio, and perceived stress from patient demands [38].…”
Section: Discussionmentioning
confidence: 99%